2022
DOI: 10.4269/ajtmh.22-0031
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices toward COVID-19 and Vaccines among Chinese Small-Town Residents: A Cross-sectional Study

Abstract: China has basically controlled the COVID-19 epidemic as a result of widespread vaccination and other containment strategies, despite localized outbreaks, as of September 2021. This study investigates the knowledge, attitudes, and practices (KAP) of COVID-19 and COVID-19 vaccines among Chinese small-town residents to provide suggestions for public health policy. Residents who were vaccinated against COVID-19 were asked to complete a paper questionnaire on KAP in Xidian, Zhejiang. The knowledge questionnaire con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…These findings align with previous studies that emphasize the impact of knowledge and attitudes on health-related behaviors. Furthermore, the positive associations observed between education level and knowledge scores, as well as between monthly household income and practice scores, are in line with previous research demonstrating the influence of socioeconomic status on health outcomes and behaviors [ 34 ]. The lower knowledge scores observed among participants in business or service careers and other occupations may indicate disparities in access to health information and resources.…”
Section: Discussionsupporting
confidence: 88%
“…These findings align with previous studies that emphasize the impact of knowledge and attitudes on health-related behaviors. Furthermore, the positive associations observed between education level and knowledge scores, as well as between monthly household income and practice scores, are in line with previous research demonstrating the influence of socioeconomic status on health outcomes and behaviors [ 34 ]. The lower knowledge scores observed among participants in business or service careers and other occupations may indicate disparities in access to health information and resources.…”
Section: Discussionsupporting
confidence: 88%
“…Medium level of vaccine-related knowledge has been noted among Chinese small-town residents. Moreover, most of the studied population wore masks outside and expressed an optimistic attitude toward the end of the pandemic ( 26 ). A survey study conducted on subjects suffering from rheumatoid arthritis confirmed the positive attitude of Chinese society toward the vaccination program, although it pointed out the low availability of vaccine doses as less than half of those willing to participate were vaccinated ( 27 ).…”
Section: Discussionmentioning
confidence: 99%